Camoulage Treatment In Facıal Asymmetry. Case Report - Enis Güray; Selçuk Basa; Ali İhya Karaman (Galenos Yayinevi, 1994)
Facial asymmetry, beside its different etiologic factors, occurs especially as a result of asymmetric growth of the mandible. For this reason, its correction is often related with the mandible. In this paper, our skeletal and dental treatment approach will be presented on one case with facial asymmetry due to the asymmetric growth of the mandible.